Human Capabilities in this Post-Neoliberal Period: A Summative Editorial - Edward P. St. John (MDPI AG, 2023)
As Professor Wang Chen noted in the introduction, this Special Issue was conceptualized after conversations concerning the prospect of an international center focused on "education development and social justice [...]